Beyond the new public management: changing ideas and practices in governance - Minogue, Martin (ed.) (Chettenham, 1998)
The 'new public management revolution' has sparked unprecedented interest in attempts to reshape and improve governance, defined as the array of ways in which the relationships between the state, society and the market is or dered. The radical public sector reform programmes of the 1980s that began in the UK, the USA, Australia and New Zealand have fostered a wave of reform in developed, developing and transitional countries, further fuelled by the collapse of the Iron Curtain and the notion that there are specific models of 'good governance' that have universal applicability.
Keywords: Civil service reform